Effects of open-label placebos across populations and outcomes: an updated systematic review and meta-analysis of randomized controlled trials - Johannes C. Fendel; Carl Tiersch; Paul Sölder; Jens Gaab; Stefan Schmidt (Scientific Reports)
Abstract This work synthesizes and updates findings from previous systematic-reviews and meta-analyses on open-label placebos (OLPs). For the first time, it directly tests whether OLPs differ in effects between clinical and non-clinical samples, and between self-report and objective outcomes. We searched eight databases up to November 9, 2023, and included 60 randomized controlled trials (RCTs), compromising 63 separate comparisons. OLPs yielded a small positive effect across various health-related outcomes (k = 63, n = 4554, SMD = 0.35, CI 95% = 0.26; 0.44, p < 0.0001, I2 = 53%). The effect differed between clinical (k = 24, n = 1383, SMD = 0.47) and non-clinical samples (k = 39, n = 3171, SMD = 0.29; Q = 4.25, p < 0.05), as well as between self-reported (k = 55, n = 3919, SMD = 0.39) and objective outcomes (k = 17, n = 1250, SMD = 0.09; Q = 7.24, p < 0.01). Neithter the level of suggestiveness nor the type of control moderated the effect. These findings confirm that OLPs are effective for both clinical and non-clinical samples—particularly when effects are assessed via self-reports.